SISTEM INFORMASI PREDIKSI JUMLAH REFILL TONER PADA PRINTER LASERJET DI CV SOERYA COM DENGAN MENGGUNAKAN METODE WEIGHTED MOVING AVERAGE BERBASIS WEB - Dwi Saputra, Septian; Mashuri, Chamdan; Zein Vitadiar, Tanhella; Ali, Mahrus (Inovate, 2024)
CV Soerya Com is a business providing printer services, laptop services, computer services and toner refills. Problems often arise when forecasting the number of toner refills in each period, because calculating toner inventory often results in a shortage or excess of toner. In this business location problem, an information system for forecasting the number of toner refills is needed. The method used in this research is the Weighted Moving Average method, namely to predict the future and each data is given a different weight from the previous data. Data generated from observations is from January 2018 to September 2023. Application using the Weighted Moving Average method (3 months) in October 2023 is 15 pcs. From the test results for the number of toner refills, the MAD, MSE and MAPE error values were 5.43, 42.50 and 36.02%. The results of the MAPE forecasting accuracy level are moderate, namely with a value of 36.02%. Keywords: Forecasting, Weighted Moving Average, MAD, MSE and MAPE.